Deležniki in njihov vpliv na izvajalca javne službe - Murtič, Emilio (Revija za univerzalno odličnost, 2025)
Research Question (RQ): Who are the key stakeholders of the municipal waste collection public service, and which of them act as stimulators or inhibitors? Purpose: We want to identify the key stakeholders of the public service provider for municipal waste collection and determine their role in shaping the work strategy. Method: The research is based on a systematic review of existing literature. The search for articles was conducted in databases such as Cobiss+, Springer Link, Scopus, Science Direct, and Google Scholar. The considered articles are from the period between 2015 and 2025, with open access and written in Slovenian or English. Results: The research has shown that the public service provider is influenced by 13 key stakeholders. These stakeholders are involved in the relationship as users of the public service provider’s municipal waste collection services, as owners of the service itself, as regulators, or as suppliers or recipients of waste. Each of them can influence the public service provider for municipal waste collection both positively and negatively. Organization: The research provides the organization with insight into key stakeholders and their impact, thus enabling the advance planning of activities for optimal execution and achievement of goals. Society: The article allows the broader public to understand the position of the public service provider for municipal waste collection among its stakeholders and how they influence the formation of the provider’s tasks, whose main purpose is to ensure basic living conditions in a given area. Originality: At the time of writing this article, such research cannot be found in Slovenia, and the knowledge gained from it allows us to understand the business and organizational environment of the service we encounter every day. Limitations / further research: The key limitation is the limited literature in this field. Most of it is in electronic form in databases. Slovenian literature is almost non-existent. Another issue is that much of the literature does not fit the specified timeframe and is therefore somewhat outdated. Due to its importance and poor research coverage, the field needed to be explored in more detail.
Keywords: deležniki; javna služba; zbiranje odpadkov